1987
DOI: 10.1002/job.4030080106
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Family conflict: The effect of job and family involvement

Abstract: A review of past research revealed inconsistent findings concerning the relationship between job involvement and work‐family conflict. This study tested whether family involvement moderates the relationship between job involvement and work‐family conflict. Two types of family involvement (spouse and parent) and two types of work‐family conflict (job‐spouse and job‐parent) were assessed. Data were gathered via questionnaire from a sample of nonteaching professionals employed by a large public university in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
14

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(131 citation statements)
references
References 16 publications
2
115
0
14
Order By: Relevance
“…In such a case, the individual may struggle balancing the demands of both roles. Frone and Rice (1987) tested this theory empirically. The authors found the effect of job involvement on inter-role conflict was only significant for those individuals who were also highly involved with their spousal role.…”
Section: Family Involvementmentioning
confidence: 99%
See 4 more Smart Citations
“…In such a case, the individual may struggle balancing the demands of both roles. Frone and Rice (1987) tested this theory empirically. The authors found the effect of job involvement on inter-role conflict was only significant for those individuals who were also highly involved with their spousal role.…”
Section: Family Involvementmentioning
confidence: 99%
“…Given the variations in affective, cognitive, and behavioral responses of sport fans (Wann & Branscombe, 1993), fan identification was chosen as the primary variable of interest. Further, research suggests role involvement/centrality is predictive of inter-role conflict (Carlson & Perrewe, 1999;Frone & Rice, 1987;Frone, Russell, & Cooper, 1992). According to the inclusion of role involvement/identification is necessary to fully understand inter-role conflict.…”
Section: Delimitationsmentioning
confidence: 99%
See 3 more Smart Citations